Copper(II) halide salts and complexes of 4-amino-2-fluoropyridine: synthesis, structure and magnetic properties. Issue 5 (4th March 2017) - Krasinski, Claire A.; Solomon, Benjamin L.; Awwadi, Firas F.; Landee, Christopher P.; Turnbull, Mark M.; Wikaira, Jan L.
Abstract: Reaction of 4-amino-2-fluoropyridine (2-F-4-AP) with copper halides produced the neutral coordination complexes: (2-F-4-AP)2 CuX2 (X = Cl(1 ), Br(2 )).1 crystallizes in the orthorhombic space group P ccn in a distorted square planar geometry. Magnetic susceptibility data were fit to the uniform chain Heisenberg model resulting in C = 0.439(6)emu-K/mole-Oe and J  = −28(1) K.2 crystallizes in the monoclinic space group C 2/m and is closer to distorted tetrahedral. Intermolecular Br⋯Cu contacts generate a square layer. Magnetic data show very weak ferromagnetic interactions [C = 0.42(1)emu-K/mol-Oe, J  = 0.71(2) K]. Similarly, reaction of 2-F-4-AP with copper halides and aqueous HX in alcohol solvents produced the salts (2-F-4-APH)2 CuX4 (X = Cl(3 ), Br(4 )).3 crystallizes in the triclinic space group P-1. Crystal packing reveals short Cl⋯Cl contacts which generate a structural ladder. However, analysis of the magnetic data suggests that only the rails of the ladder produce a viable magnetic superexchange pathway; the uniform Heisenberg chain model provides C = 0.449(1)emu-K/mol-Oe and J  = -6.9(1) K.4 is isostructural and is also best fit by a chain model [ J  = −2.7(4) K]. The brominated complex (2-F-3-Br-4-APH)2 CuBr4 ·2H2 O, 5, (2-F-3-Br-4-APH = 4-amino-3-bromo-2-fluoropyridinium) was serendipitously produced as a byproduct of the synthesis of4 and was characterized by single-crystal X-ray diffraction. Abstract :